Peranan Lembaga Peradatan Negeri dalam Penyelesaian Sengketa Tanah di Kecamatan Amahal Maluku Tengah (Lex Jurnalica, 2009)
Custom society have common law to be upheld deep shaped institutional custom, one that manage harmonious interaction among their with its ecosystem. As one of it is that still available at Moluccas Society, notably Moluccas society Intermediates that until now still gets to hold firmness to all tatanan tradition that constitute preceding forbear inheritance, If dispute happening among custom society citizen, therefore for common law society, dispute solution via non jurisdiction and working out via custom jurisdiction institute is constitute option that most commonly. conclusion who writer can pass on is as follows, that happening conflict in a general way is soiled dispute because of woolly earth bounds. Then used to law solves in a general way konflikâ€“konflik common law society happening district Amahai is with extrajudical dispute solution terminological common law system that is gone upon on peace and harmony in society life.Â Keywords: Institute,Custom Country, Conflict